Electronic structure of M(BH4)4, M = Zr, Hf, and U, by variable photon-energy photoelectron spectroscopy and density functional calculations. - Green, J; de Simone, M; Coreno, M; Jones, A; Pritchard, H; McGrady, G (2005)
Photoelectron (PE) spectra have been obtained for the M(BH(4))(4) (M = Zr, Hf and U) molecules in the 20-60 eV photon-energy range, and for M = U, also in the 90-120 eV region. Derived branching ratios (BR) and relative partial-photoionization cross sections (RPPICS) of the valence bands are used to confirm band assignment and demonstrate d-orbital covalency for all three compounds and f-orbital covalency for U(BH(4))(4). Core ionizations are identified and used to confirm resonance features in the RPPICS. The absorption spectrum of Zr(BH(4))(4) between 20 and 60 eV shows 4p absorption at 35.5 eV, coincident with the 4p-4d resonance in the RPPICS of the 1e and 2t(2) ionization bands of Zr(BH(4))(4). Less intense absorption bands at 32.5 and 33.8 eV correspond with shape resonance features in the 1a(1) and 1t(2) PE bands. The RPPICS of the f band of U(BH(4))(4) shows two strong resonant features between 95 and 120 eV. Direct photoemission of the 5f electrons from U(BH(4))(4) results only in the observation of the (2)F(5/2) ion state of [U(BH(4))(4)](+), but in the 5d-5f resonant region, a weak band corresponding to the (2)F(7/2) ion state is also observed. The splitting of the 1t(2) band of U(BH(4))(4) is attributed to a small contribution of U 6p semi-core electrons to this MO. Density functional calculations give a good estimate of the pattern of ionization energies, although the calculated absolute values are lower than the experimental values, the first IE by 0.5 eV for Zr(BH(4))(4) and Hf(BH(4))(4) and 1.0 eV for U(BH(4))(4). The MO compositions are in very good agreement with the deductions made from the BR and RPPICS analyses.